Perancangan Penambahan Kapasitas Produksi Menggunakan Studi Waktu Baku: Sebuah Studi Kasus pada PT. X - Jovan Aleysius; Nova Sepadyati (Jurnal Titra, 2022)
Responding the increasing demands, PT. X acts by increasing the production capacity as well. One of those acts is adding one burning machinery that produces Bio Septic Tanks. With this addition, adjustment of the other workstations after the burning process are expected. This paper is to answer which work stations need some adjustments to their capacity planning. Some of the methods that are being used are snapback method stopwatch time study, standard time study based on Westing House’s performance rating, allowance, and the calculation of capacity planning and adjustment of the work stations. The outcome of this paper will be given to PT. X in order to help PT. X’s capacity planning when the time comes.